Hubungan Berpikir Positif dan Komparasi Sosial dengan Ketidakpuasan Citra Tubuh pada Mahasiswi - 'Ula, Inas Fikriyatul; , Dr. Nanik Prihartanti, M.Si., Psi (2017)
This research aims to determine the relationship of positive thinking and social comparisons with body image dissatisfaction in female students. Subjects or respondents in this research is a female student Faculty of Psychology generation 2013 to 2016 which amounted to 104 subjects. Sampling is done by proportional stratified random sampling technique. The method used in this research is quantitative with measuring instruments of the scale of body image dissatisfaction, the scale of positive thinking, and the scale of social comparison. Data analysis technique used in this research is multiple linear regression analysis. Based on the result of data analysis, the correlation value of R 0,721 and significance (p) is 0,000 (p ≤ 0,01), there is very significant relation between positive thinking and social comparison with body image dissatisfaction. Another result is there is a significant negative relationship between positive thinking and body image dissatisfaction with the result of rx1y correlation of -0,177 with significance (p) of 0,050 (p ≤ 0,05). In addition there is a very significant positive relationship between social comparisons with body image dissatisfaction with a rx2y correlation of 0,641 with significance (p) of 0,000 (p ≤ 0,01). Effective contribution of positive thinking and social comparability to body image dissatisfaction of 51,9%. The level of body image dissatisfaction on the subject included in the medium category, the level of positive thinking on the subject included in the high category, while the level of social comparison on the subject included into the medium category.